Early Involvement and Integration in Construction Projects: The Benefits of DfX in Elimination of Wastes - Heikki Halttula; Harri Haapasalo; Aki Aapaoja; Samuli Manninen (International Journal of Management, Knowledge and Learning, 2017)
Typical construction processes provide waste: material waste but especially process-related waste. The majority of this waste can be avoided with efficient planning in the front end of projects. The main aim is to describe how the concept of Design for Excellence (DfX) can reduce the most severe waste in construction projects. Based on a literature review of waste and requirements that aid early involvement and integration, we created a survey for analyzing and prioritizing types of waste in the construction industry. We describe how DFX reduces this waste, especially through the use of early involvement and integration. When applied, DfX creates incentives for project stakeholders to eliminate waste automatically through early involvement and integration.